ИВО АНДРИЋ И ПОЉСКА (Prilozi za književnost, jezik, istoriju i folklor, 2024)
IVO ANDRIĆ AND POLANDThe paper analyzes Andrić’s texts in which there are motives related to Poland and its culture. At the very beginning of his literary work, during his studies in Krakow, Ivo Andrić wrote several travel notes about Poland, named Letters from Krakow and continued to insert various motives directly connected with Poland in his writings, both fictional and non-fictional. The analyzed texts show that Andrić, when writing about Poland, always basically had the thought of freedom and the need for resistance, comparing its historical fate with the fate of his homeland that was always struggling for freedom.